Language tests, linguistic gatekeeping and global mobility. Issue 3 (27th May 2019) - Hamid, M. Obaidul; Hoang, Ngoc T. H.; Kirkpatrick, Andy
ABSTRACT: Language tests are increasingly being used as gatekeeping tools in a globalised world. This article examines the processes of linguistic gatekeeping by the use of language tests in the context of migration. We draw on half a dozen cases of test-takers of the International English Language Testing System (IELTS) test who applied for entry into Australia on student, work or residency visa. We argue that while test-using migration programmes in countries such as Australia may give the impression that language tests are required for diagnosis of applicants' 'linguistic health' and certification of 'linguistic immunity', official demands of language test scores may also be only distantly related to their actual language ability. From test-takers' perspectives, the processes of linguistic gatekeeping can be linked to profit-making, suggesting how neoliberalism relates to immigration. In a neoliberal policy context, migration desires can be capitalised by gatekeeping authorities for their education and labour markets; these authorities may also capitalise on gatekeeping mechanisms such as language tests and test scores as commodified policy artefacts. Policy concerns for migrants' linguistic health may, then, be related to financial health of testing industries. The article contributes to our understanding of the relationships between language policy and globalisation by illustrating the linguistic management of global mobility in transnational migration.